Anterior knee pain - Hotfiel, T.; Engelhardt, M.; Grim, C. (Triathlon Medicine, 2019)
Anterior knee pain (AKP) as a nonspecific symptom and encompasses a broad range of different symptoms and multiple underlying functional and/or structural abnormalities. AKP is a common disorder in athletes who participate in endurance sports, particularly in triathlon that involves repetitive loading of the knee. Due to an expanding participation of the population in recreational and elite triathlon and the general high prevalence of knee pain in this sport, acute and overuse injuries of the knee are frequently observed. Most of the injuries can be related to overuse and/or functional etiology; however acute traumatic injuries may occur as well. Frequent overuse injuries of the knee include patellofemoral pain, patellar tendinopathies, plica injuries or disorders of the infrapatellar fat pad. Diagnostics for identifying the source of pain as well as a successful treatment remain challenging to ensure a successful treatment, a short time loss of training or competition and to avoid reinjuries and harmful sequelae. Addressing anterior knee pain cannot be considered in isolation to structural abnormalities, as it requires a thorough assessment of static and dynamic lower limb mechanics as well as associated risk factors. In the following chapter the most common disorders are thoroughly discussed with special attention to the underlying injury mechanisms, diagnostics, and therapeutic management.